Mekanisme Penyusunan Anggaran Pendapatan dan Belanja Desa di Desa Panda Kecamatan Palibelo Kabupaten Bima - Suryati Suryati (International Forum of Researchers and Lecturers, 2023)
This study aims: a) To find out the preparation of the Draft Village Revenue and Expenditure Budget in Panda Village, Palibelo District, Bima Regency. b) To find out the discussion and agreement of the Draft Village Revenue and Expenditure Budget in Panda Village, Palibelo District, Bima Regency, The type of research is descriptive qualitative. The data collection techniques used were interviews, observation, and documentation. The informants were the village head, secretary and staff/employees of Panda Village, administrators of village social institutions, community leaders, religious leaders, and Rukun Tetangga. Determination of informants using purposive sampling technique. The analysis technique is descriptive qualitative analysis, which starts from data reduction, data display, and verification and conclusion making: First, based on the activities of preparing the Village APB Draft as part of the mechanism or stages of preparing the Village Budget (APB) in Panda Village, the results are in accordance with the Regulation of the Minister of Villages, Development of Disadvantaged Regions and Transmigration of the Republic of Indonesia Number 7 of 2021 concerning Priorities for the Use of Village Funds in 2022, and Bima Regent Regulation Number 38 of 2018 concerning Village Financial Management).